THE ORCHESTRAL PLANE IN THE OPERA ALEXANDRU LĂPUŞNEANU BY GHEORGHE MUSTEA - GUŢANU STOIAN, Luminiţa; GUŢANU, Cătălina (Studia Universitatis Babes-Bolyai Musica, 2016)
Essentially this study aims at emphasizing the orchestral plane in the Opera”Alexandru Lăpuşneanu” by Gheorghe Mustea. The structure of the musical material is based on the thematic contrast, having a strong folk nature. The melodics of the opera proves to be greatly inventive, as it seeks effects of tone colors that are found in its ornamental mantle. In the orchestral score, the composer uses free improvisations and heterophonic elements and he actively poliphonizes the sonorous texture.